The Apocrypha of Minnie McGee:: The Murderous Mother and the Multivocal State in 20th-Century Prince Edward Island - Myers, Sharon (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2009)
Abstract In the spring of 1912, the six children of Patrick and Minnie McGee died of mysterious causes on Prince Edward Island. Minnie McGee was charged for the murder of one son and convicted of poisoning him. A case study of McGee’s subsequent life in a series of state institutions illuminates the relationship between one (admittedly extraordinary) woman and the amorphous thing called the state. While historians have often emphasized the unitary nature of the state’s disciplinary power, this case highlights the fractured features of state power, particularly within the federal system that encompassed McGee and others like her.